The Investigation that Updates Agenda of the Lithuanians Historians (About the Defense of Nerijus Babinskas Doctoral Dissertation Moldova in the Middle of 14th - Middle of 16th Centuries as a Problem of Typology of Social Structure) - Žiemelis, Darius (Lietuvos istorijos studijos, 2011)
-
Keywords: -